MULTIATTRIBUTE UTILITY THEORY, INTERTEMPORAL UTILITY, AND CORRELATION AVERSION - Andersen, Steffen; Harrison, Glenn W.; Lau, Morten I.; Rutström, E. Elisabet (International economic review (Philadelphia), 2018)
Convenient assumptions about qualitative properties of the intertemporal utility function have generated counterintuitive implications for the relationship between atemporal risk aversion and the intertemporal elasticity of substitution. If the intertemporal utility function is additively separable, then the latter two concepts are the inverse of each other. We review a theoretical specification with a long lineage in the literature on multi-attribute utility and use this theoretical structure to guide the design of a series of experiments that allow us to identify and estimate intertemporal correlation aversion. Our results show that subjects are correlation averse over lotteries with intertemporal income profiles.